The use of database linkage technique for the improvement of information on mother-infant deaths in Ceara, 2006 - Augediva Maria Jucá Pordeus; Nádia Maria Girão Saraiva de Almeida; Luciano Pamplona de Góes Cavalcanti; José Gomes Bezerra Filho; Lindélia Sobreira Coriolano (Universidade de Fortaleza, 2009)
Objective: To assess the use of database linkage technique on the improvement of information on mother-infant deaths by recovering not registered and/or ignored variables from the deaths of children under one year old, in the city of Fortaleza, in 2006. Methods: The linkage of database SIM (Mortality Information System) and SINASC (Live births Information System) was done by selecting common variables of the two systems. Using the Reclink III software there were identified the perfect pairs "Death certificate/Birth certificate" (DO/DN) by means of the variables of DO: sex, race / color, birth weight, mother's age, gestational age, type of pregnancy, type of birth, mother's occupation and mother's schooling. Results: There were registered 40,391 live births and 706 deaths of children under one year old. There were identified 516 (73.1%) DO with their respective DN. The variables occupation and mother'sm schooling increased from 31.4% and 35.8% to 64.6% and 72.8% of filling, respectively. Regarding the mother's age, the increase of information was 45.2%. Conclusion: The use of Reclink III software in the routine of health services enabled a large recovery of information that had not been fulfilled in the Death certificate (DO), and therefore, may promote a better understanding of infant mortality in studied populations.